Identificación de alteraciones oftalmológicas relacionadas con la enfermedad periodontal en canis lupus familiaris en la ciudad de machala. - Carrion Vega, Dayana Milena; Jaime Rosero, Josselyn Lisbeth (Machala : Universidad Técnica de Machala, 2023)
The main objective of this study was to identify the prevalence and type of ophthalmological alterations associated with periodontal disease in dogs of different breeds, ages, and sexes in the city of Machala. A representative sample of 60 canines, randomly selected from veterinary clinics and other locations in the city, was evaluated. The methodology consisted of a thorough physical and clinical examination, including periodontal evaluation using the plaque and calculus index (IPV), along with a detailed ophthalmological examination. This latter examination covered visual acuity measurement, tear production via the Schirmer test, and staining with fluorescein and rose bengal. Statistical analyses revealed a 75% prevalence of periodontal disease in the studied sample. A tatistically significant association was identified between the presence of periodontal disease and various ophthalmological alterations, such as dry keratoconjunctivitis, conjunctivitis, uveitis, corneal ulcers, and glaucoma. Additionally, the severity of periodontal disease was directly correlated with the severity of ocular alterations, suggesting that dogs with advanced forms of periodontal disease are at higher risk of developing severe ocular problems. The study also demonstrated that certain breeds and age groups exhibit a higher predisposition to both periodontal disease and ophthalmological alterations, indicating the need for specific preventive interventions for these groups.
El presente estudio tuvo como objetivo principal identificar la prevalencia y el tipo de alteraciones oftalmológicas asociadas con la enfermedad periodontal en perros de diferentes razas, edades y sexos en la ciudad de Machala. Se evaluó una muestra representativa de 60 caninos seleccionados aleatoriamente de clínicas veterinarias y otros puntos de la ciudad. La metodología consistió en un examen físico y clínico exhaustivo que incluyó la evaluación periodontal mediante el índice de placa y cálculo (IPV), junto con una exploración oftalmológica detallada. Esta última abarcó la medición de la agudeza visual, la producción de lágrimas mediante el test de Schirmer, y la tinción con fluoresceína y rosa de bengala. Los análisis estadísticos revelaron una prevalencia de enfermedad periodontal del 75% en la muestra estudiada. Se identificó una asociación estadísticamente significativa entre la presencia de enfermedad periodontal y diversas alteraciones oftalmológicas, como queratoconjuntivitis seca, conjuntivitis, uveítis, úlceras corneales y glaucoma. Además, se encontró que la severidad de la enfermedad periodontal correlaciona directamente con la gravedad de las alteraciones oculares, sugiriendo que perros con formas avanzadas de enfermedad periodontal tienen un mayor riesgo de desarrollar problemas oculares graves. El estudio también demostró que ciertos grupos de razas y edades presentan una mayor predisposición tanto a la enfermedad periodontal como a las alteraciones oftalmológicas, indicando la necesidad de intervenciones preventivas específicas para estos grupos.
Keywords: ENFERMEDAD PERIODONTAL; ALTERACIONES OFTALMOLOGICAS; QUERATOCONJUNTIVITIS SECA; ULCERAS CORNEALES